Post-Humanitarianism: Governing Precarity through Adaptive Design. Issue 1 (1st January 2019) - Duffield, Mark
Abstract : This paper provides a critical analysis of post-humanitarianism with reference to adaptive design. At a time when precarity has become a global phenomenon, the design principle has sidelined the need for, or even the possibility of, political change. Rather than working to eliminate precarity, post-humanitarianism is implicated in its reproduction and governance. Central here is a historic change in how the human condition is understood. The rational Homo economicus of modernism has been replaced by progressive neoliberalism's cognitively challenged and necessarily ignorant Homo inscius . Solidarity with the vulnerable has given way to conditional empathy. Rather than structural outcomes to be protected against, not only are humanitarian crises now seen as unavoidable, they have become positively developmental. Post-humanitarianism no longer provides material assistance – its aim is to change the behaviour of the precariat in order to optimise its social reproduction. Together with the construction of logistical mega-corridors, this process is part of late-capitalism's incorporation of the vast informal economies of the global South. Building on progressive neoliberalism's antipathy towards formal structures and professional standards, through a combination of behavioural economics, cognitive manipulation and smart technology, post-humanitarianism is actively involved in the elimination of the very power to resist.